Optimasi Kinerja Mesin Press dan Mesin Pemotong Produksi Sekop Menggunakan Metode OEE dan RCM pada PT XY - Angga Dwi Laksa; Herlina Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
A serious operational challenge is the high downtime rate of two machine types: the press and the cutting machine. This condition causes production targets to be missed and efficiency levels to drop sharply. OEE evaluates three critical pillars: machine availability, performance, and output quality. Furthermore, the Six Big Losses method is employed to trace the most dominant root causes. Meanwhile, RCM is applied to formulate a maintenance plan guided by failure modes of components. Field findings show that the average availability of the press machine is 85.5%, while the cutting machine reaches 89.2%. The primary triggers of downtime are component failures: overheated motors, unresponsive sensors, worn dies, leaking hydraulic seals, and dull blades. Based on RCM data processing, systematic preventive maintenance actions are recommended to reduce idle time and boost machine efficiency.